Spectral analysis of UWB multiple access schemes using random scrambling. - Cassioli, D. (IEEE Transactions on wireless communications)
With the new release of the Federal Communication Commission on matters of regulation of marketing and operation of ultra-wideband (UWB) devices, an analytical framework to enable tractable analysis of the spectrum shape of these signals is needed. We extend the framework introduced by W. A. Gardner to the case of UWB signals. We introduce a generalized UWB signal model that can be specialized to represent the traditional time-hopping (TH) technique as well as the alternative multiple access technique that we indicate as delay coded sequence (DCS). The DCS technique resembles the traditional direct sequence spread spectrum techniques, but it is not based on pulse polarity inversion. The considered matrix signal formulation allows us to easily evaluate the spectral characteristics of UWB signals under many different operating conditions: continuous or discontinuous transmissions, random or periodic scrambling operations, with or without jitter. We evaluate the spectrum of the general UWB signal under the random scrambling assumption, then we specialize it to the TH and DCS cases and discuss the variability of the spectra to some critical design parameters. We obtain an asymptotic expression of the general UWB spectrum that we use to evaluate the UWB interference power at the output of a generic receiver.